The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1997
DOI: 10.1007/s004250050191
|View full text |Cite
|
Sign up to set email alerts
|

Vision in microalgae

Abstract: Flagellate green algae such as Chlamydomonas and related genera are guided by their eyes to places where light conditions are optimal for photosynthetic growth. These eyes constitute the simplest and most common visual system found in nature. The eyes contain optics, photoreceptors and the elementary components of a signal-transduction chain. Rhodopsin serves as the photoreceptor, as it does in animal vision. Upon light stimulation, its all-trans-retinal chromophore isomerizes into 13-cis and activates a photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(64 citation statements)
references
References 58 publications
1
62
0
1
Order By: Relevance
“…Chlamydomonas , the all-transretinal polyene chromophore isomerizes upon light stimulation to 13-cis and activates a photoreceptor channel, leading to a rapid Ca 2 + influx into the eyespot region. The Ca 2 + fluxes represent the molecular basis for phototaxis (Hagemann, 1997). Recently, a new type of rhodopsin, channelrhodopsin, has been reported from Chlamydomonas reinhardtii .…”
Section: Introductionmentioning
confidence: 99%
“…Chlamydomonas , the all-transretinal polyene chromophore isomerizes upon light stimulation to 13-cis and activates a photoreceptor channel, leading to a rapid Ca 2 + influx into the eyespot region. The Ca 2 + fluxes represent the molecular basis for phototaxis (Hagemann, 1997). Recently, a new type of rhodopsin, channelrhodopsin, has been reported from Chlamydomonas reinhardtii .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, anomalous concentrations of RAs and 4-oxoRAs (up to 20 ng/L) were measured in some protected drinking water sources (30), which suggested that there might be unidentified sources of RAs in aquatic systems. There are some reports on the existence of retinal, one of the precursors of RAs, in algae, and isomerization of the all-trans-retinal chromophore into 13-cis-retinal activated the photoreceptor channel, whereas RAs were not associated with photoreceptors in algae (31)(32)(33). The nonanimal hydroxylase enzyme (CYP120A1) in the cyanobacteria Synechocystis was reported to be capable of converting RAs to corresponding hydroxyl derivatives (34), and a hydroxylated RA, 7-OH-RA, has recently been observed in several species of cyanobacteria (35).…”
mentioning
confidence: 99%
“…Fitting with a sum of two saturating functions reveals a slower low-light-saturating current and faster high-light-saturating current (9-11, 16, 17), which were interpreted as being driven by either a single, or two different, photoreceptor proteins (18). Multiple photoreceptors have been considered, based on the complex shape of the photoreceptorcurrent action spectrum (8,11,14), and results from retinalreconstitution studies (19).For several years the most abundant protein in the eyespot membranes of Chlamydomonas and Volvox has been considered as the photoreceptor for photomotile responses in these algae (20,21). However, recently the so-called ''chlamyrhodopsin'' (21) has been ruled out as the photoreceptor pigment for either phototaxis or the photophobic response in Chlamydomonas (22).…”
mentioning
confidence: 99%